Comparing the public sphere in social networking services during a period of political upheaval: The three news channels' Facebook accounts in the 2016 South Korean Presidential scandal. (1st November 2017) - Song, Dong Hyun; Son, Chang Yong
This article examines the role of the social network services (SNSs) in constructing an online public sphere during a period of political upheaval. From October 2016 to March 2017, Korean politics was scandalized by former President Park Geun-hye's legal malfeasance. It was revealed in October 2016 that she had shared classified documents with her friend, Ms Choi Soon-Sil, who had used her relationship with the president for her own political gain. The public demanded the president's resignation, and the SNSs such as Facebook, Twitter and YouTube played a significant role in delivering information about Park Geun-hye's corruption. The article investigates the social networking sites' roles in forming an online public sphere. It focuses its attention on the three South Korean television news channels' Joongang Tongyang Broadcasting Company (JTBC), the Munhwa Broadcasting Corporation (MBC) and the Korean Broadcasting System (KBS) Facebook accounts. The article contends that only the JTBC provided a significant platform for online critical engagement during the scandal compared with MBC and KBS.